Sedation for transesophageal echocardiography: comparison of propofol, midazolam and midazolam-alfentanil combination - Toman Huseyin; Atakan Erkılınc; Tuncer Kocak; Fusun Guzelmeric; Omer Faruk Savluk; Mevlut Dogukan; Goksel Acar (Medicinski glasnik, 2016)
Aim: The administration of trans esophageal echocardiography (TEE) may cause nausea, shortness of breath, agitation, emotional distress and pain in patients due to pharyngo-esophageal intubation, which may be partially relieved by sedoanalgesia. The aim of this study was to compare clinical effects of midazolam, midazolam-alfentanil combination and propofol sedation given for sedation and sedoanalgesia to patients with planned diagnostic TEE interventions. Methods: This study was prospectively completed with 90 randomized adult patients in ASA risk groups I-II-III. Group M were given 2.5 mg midazolam, group MA were given 1 mg midazolam and 5 ?g/kg alfentanil and group P were given 0.5 mg/kg propofol intravenous bolus. If necessary, additional doses were administered. Patients administered with TEE were evaluated in terms of additional dose requirements, Ramsey Sedation Scale (RSS), modified Aldrete Scoring (MAS), recovery time and duration of stay in the hospital. Results: In the group P additional dose requirements were greater (p<0.05), as well as the duration of stay in the recovery unit and hospital were shorter (p<0.05). On insertion of the TEE probe, the RSS in the group P was clearly higher than in other groups M and MA (p<0.05). Conclusion: During the TEE intervention, the use of propofol, contrary to requirements for additional dose and observation of apnea, appears to be advantageous due to providing more rapid and effective sedation depth without a need of expensive antagonist agents, and allowing early discharge of patients. Additionally, it seems that the use of midazolam combined with alfentanil, is more advantageous comparing to midazolam alone.
Keywords: propofol; midazolam; alfentanil; outpatient